Essentials of strength training and conditioning - 4 0 16; 1943-;1967- Baechle, Thomas R.,;Earle, Roger W.; 5 National Strength & Conditioning Association (U.S.) (Champaign, IL : Human Kinetics, 2008)
Presents a comprehensive manual for those preparing for the NSCA Certified Personal Trainer examination and contains over three hundred illustrated color photographs and information on the concepts and applications of exercise sciences, testing and evaluation, and exercise techniques.
Includes bibliographical references (p. 591-630) and index.
Keywords: 2 -- 0; 6; Physiological aspects. -- Physical education.;Muscles.;Physical fitness; 20; 2